Argosfestival 2004. - Assenmaker, Michel; Gutierez, Laurent; Hou, Hanru; LaBelle, Brandon; Lageira, Jacinto; McElhatten, Mark; Ou, Ning; Portefaix, Valérie; Sichel, Berta; Sterken, Sven; Stevenheydens, Ive (Brussel : Argos Editions, 2004)
Abendroth, Manuel ; André, Marie ; Asselberghs, Herman ; Aubier, Stéphane ; Baes, Pascal ; Baillif, Olga ; Beaubois, Franck ; Bianconi, Loredana ; Boutique Vizique ; Bucquoy, Jan ; Burki, Marie José ; Canto Vila Varinia ; Cargo vzw ; Carlier, Stephanie ; Carlos Iglesias Echeverri, Jose ; Case, Charley ; Cash, Robert ; Catrysse, Wim ; Cattelain, Claude ; Christiaens, Xavier ; Code 31 ; Convert, Jean-Philippe ; Coppin, Christian ; Crouwers, Alexandra ; Debackere, Brecht ; De Bemels, Antonin ; de Boer, Manon ; De Clerck, Alain ; De Clercq, Anouk ; Decock, Jérome ; Decostere, Stefaan ; De Gruyter, Jos ; Delayen, Eric ; de Pierpont, Philippe ; de Soto, Olga ; De Volder, Geoffroy ; D'Haeseleer, Kurt ; Downsbrough, Peter ; Ducat, François ; Dufranne, Nicolas ; Dumon, Dirk ; Dundic, Emmanuel ; Evermore, Alice ; Foam ; Gaillard, Frédéric ; Garcia Rubio, Pablo ; Geronnez, Alain ; Gigounon, Bernard ; Giloux, Pierre-Jean ; Gomez Marin, Daniel ; Heiremans, Ronny ; Heremans, Pieter ; Howe, Sarah Moon ; IBWT ; Image Z[one] ; Janssens, Ann Veronica ; Janssens de Bisthoven, Sylvie ; Jantar, Maja ; Jashari, Shelbatra ; Jean, Patric ; Khleifi, Michel ; Knorr, Ulrike ; Krikri ; LAB[au] ; Leper, Hendrik ; Leroy, Annik ; Lester, Gabriël ; Lizene, Jacques ; Looking Glass ; Lopez-Menchero, Emilio ; Maes, Annemie ; Martin, Isabelle ; Martin, Marie-France & Patricia ; Meander, Jelle ; Medrano Castrillon, Mauricio ; Messieurs Delmotte ; Mulliez, Bernard ; Nadine ; Nouzha, Isabelle ; Nys, Sophie ; Opsomer, Els ; Osuskiewiza, Piotr ; Pacquée, Ria ; Patar, Vincent ; Pawlowski, Mauro ; Plenevaux, Alexandre ; Provost, Nicolas ; Schiffeleers, Stijn ; Sebti, Yacine ; Simoens, Tommy ; Sivan, Eyal ; Sojcher, Frederic ; Suermondt, Robert ; Suzuki, Ai ; Theys, Koen ; Thys, Harald ; etc.
Argosfestival 2004, Brussel, 15 - 23/10/2004
boek